Effect of surface tension on the measurement of surface energy components of asphalt binders using the Wilhelmy Plate Method. (15th November 2015) - Luo, Rong; Zhang, Derun; Zeng, Zhe; Lytton, Robert L.
Highlights: Present configurations of the Wilhelmy Plate Test with the curved liquid surface. Develop models for the variation of the immersed length due to surface curvature. Identify significant variations in contact angles distinctly different from 90°. Quantify variations in surface energies when considering the curve liquid surface. Abstract: The Wilhelmy Plate Method has been widely used to determine the surface energy components of asphalt binders. When performing the Wilhelmy Plate Test, the distance from the liquid surface to the bottom of the asphalt-coated plate, h′, is usually taken as the immersed length of the plate. However, the actual immersed length of the test sample is different from h′ as long as the contact angle is not 90° because of the curved liquid surface due to surface tension at the air–liquid interface. This paper investigates the effect of the curved liquid surface on the contact angle measurements and on the corresponding surface energy components in the Wilhelmy Plate Test. Mathematical models were developed for the variation of the immersed length of the test samples when the contact angle is obtuse, right and acute, respectively. The Wilhelmy Plate Test was performed on two asphalt binders to determine the contact angles with and without considering the curved liquid surface. The cohesive bond energies of the two asphalt binders were therefore evaluated, as well as the adhesive bond energy between each asphalt and a type of gravel aggregates selected from the literature. The measurements and analysis showed that considering the curved liquid surface led to significant variations in: (1) contact angles much larger or much smaller than 90°; (2) most surface energy components calculated based on the contact angles; and (3) half of the cohesive bond energy components. This study refines the Wilhelmy Plate Method for its application to asphalt binders. The data analysis protocol newly developed in this paper has the capability of determining the contact angles and surface energy components more accurately with considering the curved liquid surface due surface tension at the air–liquid surface.